Systematic fiscal policy and macroeconomic performance: A critical overview of the literature - Claire Reicher (Kiel Institute for the World Economy (IfW), 2014)
The literature on systematic fiscal policy and macroeconomic performance in industrialized countries is large but fragmented. Based on a broad overview of that literature, several patterns emerge. The empirical literature points toward strongly anticyclical policy, which consists of procyclical tax revenues, acyclical tax rates and government purchases, and countercyclical transfer payments. Consolidation in response to the debt has come primarily through adjustments to taxes and possibly purchases. Furthermore, a large government is associated with reduced macroeconomic volatility. The theoretical literature on anticyclical fiscal policy, meanwhile, has gone from mostly focusing on government purchases and tax rates toward beginning to focus on transfer payments, although more quantitative work remains to be done in linking theory with empirics. At the same time, a policy literature has begun to develop, which has applied lessons from the theoretical literature in order to understand different consolidation scenarios and different proposed fiscal rules, particularly in Europe.
Keywords: E62; E63; H30; 330; fiscal policy; fiscal rule; fiscal response function; deficits; taxes; government purchases; transfer payments